Demographic, clinical and lifestyle predictors for severity of erectile dysfunction and biomarkers level in Malaysian patients - Mark, Raymond; Huri, Hasniza Zaman; Razack, Azad Hassan Abdul (Universidade de Sao Paulo, 2018)
The incidence of erectile dysfunction (ED) is rising worldwide and its prevalence is one of the main health concerns that affect overall men well-being in Malaysia. The cluster of demographic, clinical and lifestyle factors may have contributed to the severity of ED and changes in biomarkers level; nevertheless these have not been studied extensively. This cross sectional study involved a total of 276 patients with 138 was diagnosed with ED. The demographic, clinical, lifestyle factors and severity of ED were assessed using a set of questionnaire and the International Index of Erectile Function (IIEF-5). Meanwhile, Total Testosterone (TT) and Asymmetric dimethylarginine (ADMA) levels were determined using the enzyme-linked immunosorbant assay (ELISA). Binary logistic regression test was used to demonstrate the predictors of severity of ED, TT and ADMA levels. Significant predictors for worsening of severity of ED are self-employed [10.55 (0.43 – 257.06), p=0.004], pensioner [8.07 (0.19 – 352.45), p=0.026], non-government employee [1.16 (0.05 – 26.26), p=0.04] and TT [0.41 (0.25 – 0.69), p=0.001]. Nevertheless, pensioner [0.08 (0.01 – 0.87), p=0.038] and unemployed [0.04 (0.01 – 0.42), p=0.007], were the predictors that may influence the changes of TT levels. On the other hand, academic qualification (secondary) [4.51 (0.48 – 42.83), p=0.014] and intensity of physical activities (< 1 hour/day) [2.61 (0.65 – 10.48), p=0.008] were the predictors which were more likely to influence the changes of ADMA levels in ED patients. TT and ADMA levels were influenced by demographic and lifestyle factors whilst severity of ED was predicted by demographic and clinical factors in Malaysian ED population. These predictors may provide new knowledge on risk factors of severity of ED and help in management of ED. Thus, the predictive models could serve as a primary guidance to physicians to ensure ED being managed and treated more effectively.